A constituição de sentidos e sujeitos na relação entre o português brasileiro e o yorùbá nas práticas litúrgicas do Ilê Axé Ojú Obá Odé em Pernambuco - Silva, Louise Adélia Gama (Universidade Federal de São Carlos, 2025)
In a historical context marked by the repression and erasure of African languages, replaced by the imposition of an official language, European Portuguese, we propose the following question: How does semantic functioning, through the articulation of these two languages, constitute meanings and subjects on the basis of liturgical practices in contemporary Candomblé? We consider that, although Brazil is a country whose social and cultural formation was deeply shaped by African matrices, the presence of African languages has been systematically silenced, often being restricted to religious practices. In this sense, this study seeks to understand, from the theoretical perspective of the Semantics of the Event, developed by Guimarães (2002, 2018), how the relationship between the Portuguese language spoken in Brazil, the African language Yorùbá, and the subjects who speak these languages is constituted. To this end, we take as our object of analysis a recording of a saída de santo from a Candomblé house in the state of Pernambuco, available on the YouTube platform. This corpus allows us to observe, through the enunciative excerpts selected, how meanings and subjects are constituted within this liturgical space, in which the alternation between Brazilian Portuguese and Yorùbá operates by activating different memorables within the language event, producing specific meanings and resignifying collective identities.The methodology adopted is grounded in the analysis of enunciative scenes, privileging the description of enunciative spaces and the relational dynamics between the languages. We understand that this approach is fundamental for capturing how historical processes of erasure and resistance are concretely updated in religious practices, revealing specific forms of interaction and meaning production that characterize these language events. We consider the historical dimension to be constitutive of both languages and speaking subjects, making it essential to reflect on how this historicity traverses the relationship between the two languages, contributing, or not, to specific forms of interaction between them and to the production of meaning. Thus, this research is justified by its social and academic relevance, as it describes and analyzes how the articulation between Brazilian Portuguese and Yorùbá is configured in the enunciative excerpts analyzed within an African-matrix liturgical space. In doing so, we seek to highlight the persistence and potency of African languages in contemporary Brazil, as well as to reflect on the ways in which this relationship affects the identity and subjective constitution of practitioners of this religion.
The construction of meanings and subjects in the relationship between brazilian portuguese and yorùbá within the liturgical practices of Ilê Axé Ojú Obá Odé in Pernambuco
Keywords: Yorùbá; Candomblé; Acontecimento enunciativo; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; 4. Educação de Qualidade